2019
DOI: 10.3390/economies7010023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Real Exchange Rate on the Finance-Growth Nexus in the West African Region

Abstract: This study examines the moderating effects of the real exchange rate and its volatility on the finance-growth nexus in the West African region. It also determines the marginal effects of financial development on economic growth at various levels of the real exchange rates and its volatility. The findings show that financial development has a long-term positive impact on economic growth, but this impact is weakened by real exchange rate and its volatility. The marginal effects of financial development on econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…Chiang (2019) studied monthly data from 15 stock markets, along with economic policy uncertainty (EPU) as a news variable, and found that news is able to predict stock market future returns. Ehigiamusoe and Lean (2019) pointed out that financial development has a long-term positive impact on economic growth, while the real exchange rate and its volatility weaken this impact. The development of the financial sector will not bring ideal economic benefits unless it is accompanied by the decline and stability of the real exchange rate.…”
Section: Explaining Market Efficiency In Subdividing Areasmentioning
confidence: 99%
“…Chiang (2019) studied monthly data from 15 stock markets, along with economic policy uncertainty (EPU) as a news variable, and found that news is able to predict stock market future returns. Ehigiamusoe and Lean (2019) pointed out that financial development has a long-term positive impact on economic growth, while the real exchange rate and its volatility weaken this impact. The development of the financial sector will not bring ideal economic benefits unless it is accompanied by the decline and stability of the real exchange rate.…”
Section: Explaining Market Efficiency In Subdividing Areasmentioning
confidence: 99%
“…Nonetheless, the frontier of recent literature is shifting towards the examination of the variables that could influence the finance‐growth nexus. The impact of finance on growth could be influenced by the quality of institutions, level of income, level of financial deepening, structure of the financial system, real exchange rate and inflation rate (Ehigiamusoe and Lean, ; Ehigiamusoe et al , ; Law et al , ). But the influence of economic union on the finance‐growth nexus has not been given adequate consideration in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Inflation is expressed as the percentage change in the aggregate price level over a period of time, typically a year (Ball, 2011). Ehigiamusoe & Lean (2019) expressed the inflation rate as macroeconomic instability.…”
Section: Introductionmentioning
confidence: 99%